Vascular endothelial growth factor (VEGF), transforming growth factor beta (TGFβ), angiostatin, and endostatin are increased in radiotherapy-induced gastrointestinal toxicity. (31st May 2018) - Stansborough, Romany L.; Bateman, Emma H.; Al-Dasooqi, Noor; Bowen, Joanne M.; Wignall, Anthony; Keefe, Dorothy M.; Yeoh, Ann S.; Logan, Richard M.; Yeoh, Eric E. K.; Stringer, Andrea M.; Gibson, Rachel J.
Abstract: Purpose: Radiotherapy-induced gut toxicity (RIGT) is a debilitating effect of radiotherapy for cancer, often resulting in significant diarrhea and pain. Previous studies have highlighted roles of the intestinal microvasculature and matrix metalloproteinases (MMPs) in the development of RIGT. We hypothesized vascular mediators would be significantly altered in a dark agouti (DA) rat model of RIGT. Additionally, we aimed to assess the effect of MMP-2 and -9 inhibition on the response of tumor-associated microvascular endothelial cells (TAMECs) to radiation. Methods: DA rats were administered 2.5 Gy abdominal irradiation (3 times/week over 6 weeks). Vascular endothelial growth factor (VEGF), transforming growth factor beta (TGFβ), von Willebrand factor (VWF), angiostatin, and endostatin expression was assessed at 3, 6, and 15 weeks. Additionally, DA rat mammary adenocarcinoma tumor-associated microvascular endothelial cells (TAMECs) were used to assess the effects of radiation (12 Gy) and the MMP inhibitor SB-3CT on MMP, VEGF, and TGFβ expression, and cell viability. Results: VEGF mRNA expression was significantly increased in the colon at week 15 ( p  = .0012), and TGFβ mRNA expression was significantly increased in both the jejunum and colon at week 3 ( p  = .0280 and p  = .0310, respectively). Endostatin immunostaining was significantly increased at week 3 ( p  = .0046), and angiostatin at 3 and 6 weeks ( p  = .0022 and p  = .0135, respectively). MMP-2 and -9 mRNA and total protein levels were significantly increased following irradiation of TAMECs. Although this increase was significantly attenuated by SB-3CT, it did not significantly alter endothelial cell viability or VEGF and TGFβ mRNA expression. Conclusions: Findings of this study support the involvement of VEGF, TGFβ, angiostatin, endostatin, and MMP-2 in the pathobiology of RIGT. However, the relationship between these mediators is complex and needs further investigation to improve understanding of their therapeutic potential in RIGT.